Comparison of headspace-SPME-GC–MS and LC–MS for the detection and quantification of coumarin, vanillin, and ethyl vanillin in vanilla extract products - De Jager, Lowri S.; Perfetti, Gracia A.; Diachenko, Gregory W. (Food chemistry, 2008)
A headspace-solid phase micro-extraction (HS-SPME) GC–MS method has been developed for the determination of coumarin, vanillin and ethyl vanillin in vanilla products. Limits of detection ranged from 1.33 to 13.2 ng mL −1. Accuracy and precision data for the method were measured and compared to those obtained using LC-ESI-MS. A survey of 24 commercially available vanilla products was completed using both techniques. No coumarin was detected in any of the samples. Examination of the GC–MS chromatograms revealed the presence of 18 other flavor related compounds in the samples. The method validation and sample analysis data using HS-SPME-GC–MS were comparable to those obtained using the LC–MS method. Because the two methods are conceptually different from one another, both methods would not be subject to the same interferences. This would allow them to be used as confirmatory methods for each other.